Knowledge and stigma of depression among adolescents in Indonesia: a cross-sectional study - Sarfika, Rika; Permata, Putri Indah; Mailani, Fitri; Wijaya, Nindy Eka; Saifudin, I Made Moh. Yanuar; Efendi, Ferry (International Journal of Public Health Science (IJPHS), 2024)
Depression is a prevalent mental health issue among Indonesian adolescents. Adolescents grappling with depression face various challenges, including exclusion, discrimination, educational difficulties, and violations of human rights. Limited knowledge about depression contributes to stigma, which impacts teenagers' reluctance to seek professional help. This study aimed to examine the correlation between adolescents' knowledge and the stigma of depression. Using a cross-sectional framework, this study involved 240 high school students from grades 10, 11, and 12. All participants completed and returned the requisite instruments. Knowledge about depression was assessed using the adolescent depression knowledge questionnaire (ADKQ), while the depression stigma scale (DSS) was used to gauge levels of stigma. The relationship between knowledge and stigma was analysed using the Spearman rank test. The findings indicate that the mean score for adolescents' knowledge about depression was 7.00 (SD=2.72), while the mean score for stigmatisation of depression was 42.02 (SD=8.43). A significant relationship between knowledge and stigma was observed (p<0.0001), characterised by moderate strength and a negative direction (r=-0.45). The study concludes that more excellent knowledge about depression among adolescents is inversely related to the level of the stigma they harbour. It is therefore recommended that mental health nurses in Community Health Centers enhance educational and counselling programs to inform adolescents about depression better. Collaboration between academic institutions and healthcare facilities, along with the development of school-based mental health programs, is imperative for reducing the stigma associated with depression among students.